Podzemelj – an Iron Age centre in Bela krajina, in the light of new research - Grahek, Lucija; Kovač Otmar (Arheološki vestnik, 2020)
The present paper is focused on archaeological research at the Iron Age centre at Podzemelj. Recent research at the southern summit of the Kučar hillfort and the discovery of a burial ground at Pezdirčeva njiva, at the western foothill, significantly complements our knowledge about the development of the Iron Age in the Bela krajina region. At the outset, the article showcases all of the past archaeological research on both the settlement and the associated burial grounds. Within the first, the latest settlement excavations at the southern summit of the hillfort Kučar unearthed two phases of the Hallstatt period settlement. For the first time, the remains of a defensive embankment were investigated, most probably the remnants of an enclosing wall of this part of the settlement. Traces of the Late Iron Age phase were also identified in this area. At the cemetery, which has not yet been explored in its entirety, two clusters of graves were discovered, with the first one dating to the Late Hallstatt period and the second belonging to the Vinica group to the Late Iron Age. The research on both locations within the prehistoric Podzemelj complex is still ongoing and will be comprehensively presented in the near future.